PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DENGAN MODEL PEMBELAJARAN LANGSUNG PADA MATERI KUBUS DAN BALOK DI KELAS VIII MTS NU AL-FALAH KUSAN HILIR - Syaiful Bahri (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
The purpose of this study was to determine the learning outcomes of students using model Cooperative type Make a Match, knowing the results of student learning using Learning model Direct and to determine whether there is a significant difference of student learning outcomes using model Cooperative type Make a Match with Learning model direct MTs NU Al-Falah Kusan Hilir. The method used in this study is quasi-experimental. The research sample consisted of 48 students of class VIII A as the control class and as many as 24 students and class VIII B as the experimental class with 24 students. The data collection technique using multiple choice tests. The trial results showed that the test has been qualified validity and reliability. Data analysis was performed in the study was an average, standard deviation, normality test, homogeneity test and t-test. The results of this study are student learning outcomes in class experiments had an average of 72.92 and the control class has an average value of 74.79. The research result shows t = -0.58 and then thitung table = 2.014 <t table then H0 is accepted that there are no significant differences in learning outcomes between the type cooperative learning model Make a Match with Direct Learning model. Keywords: Comparison of the results of learning, Learning Model Make a Match, Live Learning Model.